Effect of Accuracy and Muscle Strength Training on the Result of Shooting Throws in Petanque - badaru, Benny; Rachmat Kasmad, Muhammad; Juhanis, Juhanis; Anwar, Nur Indah (Universitas Suryakancana, 2021)
This study aims to determine: The effect of which exercise is better, between precision training and arm strength training on the results of shooting shots at petanque athletes. This research is an experimental research in the form of one-group pretest-postest design design. The population and sample in this study were South Sulawesi athlete athletes with a total of 16 athletes, the technique of determining samples using saturated samples. The data analysis technique used was descriptive statistics. The results showed that: (1) the strength treatment group trained by push up exercises significantly influenced the shooting results of South Sulawesi petanque athletes, the effect seen from the increase in results from the initial test to the final test was 19,147. (2) the treatment group trained by throwing bosi on the tires and throwing bosi with beam barriers had a significant effect on the shooting results of South Sulawesi petanque athletes, so that the effect of improvement was seen from the results of the initial test to the final test of 6.206. The conclusion of the study is that arm muscle strength training has a more significant effect on shooting throw compared to accuracy training, it can be seen from the magnitude of the increase in value obtained from the arm muscle strength experimental group.Â Keywords: Training, Accuracy, strength, shooting and petanqueÂ